Teaching Marcuse - James, Beverly Ann (Javnost (Ljubljana), 2006)
Herbert Marcuse's 1964 classic, One-Dimensional Man, was required reading for that generation of scholars who came of age intellectually in the era epitomised by 1968. The most widely read of Marcuse's sixteen major books, One-Dimensional Man led the New York Times to identify Marcuse as "the foremost literary symbol of the New Left." Over the decades, however, with the dumbing down of American higher education and the commodification of learning, Marcuse fell out of favour. This article argues that One-DimensionalMan is highly relevant to the current generation of students and provides them with theoretical concepts for understanding contemporary problems. The trends Marcuse described in the 1960s have accelerated, so that his basic arguments are more relevant than ever for courses in news, advertising, and contemporary culture. Marcuse relies heavily on examples to advance his arguments, and this article demonstrates for his illustrations can easily be brought up to date. Following the author's background notes on Marcuse and basic Marxist concepts, the article identifies five suggestive themes that can be drawn from the text to consider contemporary problems: true versus false needs, lack of class consciousness, alliance between government and business, militarism, and authoritarian language.
Keywords: Herbert, Marcuse, 1898-1979; sociološke teorije; socialna filozofija; 20.st.; civilizacija; civilization; industrijska družba; kapital; Das Kapital; potrošništvo; vrednote